Surgical management of complicated duplex kidney: A tertiary referral centre 10-year experience - Irene Paraboschi; Federica Farneti; Guglielmo Mantica; Patil Kalpana; Arash Tagizadeh; Paul Anu; Mishra Pankaj; Massimo Garriboli (Wolters Kluwer Medknow Publications, 2023)
Aim: The management of a complicated duplex kidney remains a challenge for paediatric urologists. The aim of this study is to report a 10-year experience of the surgical management of complicated duplex kidney in a single tertiary care paediatric referring hospital. Materials and Methods: Clinical records of all children who undergone a surgical procedure for complicated duplex systems between January 2009 and March 2019 at our institution were retrospectively reviewed. Clinical manifestations, surgical procedures, complications and follow-up were collected and analysed. Logistic regression was performed to explore if any patient's characteristic or underlying associated comorbidity (ureterocoele, ectopic ureter, obstruction, etc.,) could be positively linked to the chance to develop recurrent urinary tract infections (UTIs). Results: We have identified 95 children who received a surgical treatment for 102 complicated duplex kidneys. The presence of an ureterocoele was recorded in 41 (43.2%) patients, an ectopic ureter in 25 (26.3%), a vesicoureteral reflux (VUR) in 40 (42.1%), a vesicoureteric junction obstruction in 24 (25.3%) and an ureteropelvic junction obstruction in 3 (3.2%). An invasive approach such as an heminephrectomy (71.6%) was required in the majority of cases. Higher risk of developing a UTI has been demonstrated in children diagnosed postnatally (P < 0.001) and in those with an associated obstruction (P < 0.05). Conclusions: No standardised management could be recommended for the surgical treatment of complicated duplex kidney. Children without antenatal diagnosis and with either an upper tract obstruction or VUR are at greater risk to develop UTI and need to be looked after more closely.